2014
DOI: 10.1177/0957650914540153
|View full text |Cite
|
Sign up to set email alerts
|

Stall margin improvement of a centrifugal compressor utilizing various stepped tip gap configurations

Abstract: Aerodynamic performance of a centrifugal compressor is investigated under various casing treatment configurations of stepped tip gap type, numerically. This technique is introduced as an effective method for improvement of compressor stall margin and consequent enhancement of the compressor overall performance. In this respect, flow field within the proposed compressor was simulated by solving the Navier–Stokes equations utilizing the well-known k-ɛ turbulence model. Different geometries of the compressor step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Taghavi-Zenouz et al. 1 researched various casing treatment configurations of the stepped tip-gap type and found them to be an effective method for improving the compressor stall margin. Li et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taghavi-Zenouz et al. 1 researched various casing treatment configurations of the stepped tip-gap type and found them to be an effective method for improving the compressor stall margin. Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some interesting phenomena had been found in the study of compressor TLF characteristics. Taghavi-Zenouz et al 1 researched various casing treatment configurations of the stepped tipgap type and found them to be an effective method for improving the compressor stall margin. Li et al 2 studied the effect of chordwise nonuniform tip clearance on axial-compressor performance and found that by reducing the leading edge (LE) clearance size and increasing the trailing edge (TE) clearance size, the flow rate of a compressor was increased and the flow separation was delayed near the TE of the blade suction surface (SS).…”
Section: Introductionmentioning
confidence: 99%
“…They found that, for same amount of flow coefficient, by shifting the shroud contour in the axial direction, head In the meridional direction of the passage, trimming is restricted by choking and hence a reduction up to 15% in head coefficient was achieved. Aerodynamic performance of a centrifugal compressor was investigated under various casing treatment configurations of stepped tip gap type numerically by Reza TaghaviZenouz [7]. This technique was introduced for the improvement of stall margin and efficiency.…”
Section: Introductionmentioning
confidence: 99%